EKSPLORASI POTENSI TAMAN NASIONAL KOMODO: PENDEKATAN PENGEMBANGAN PAKET WISATA BERBASIS WISATA BAHARI - Hens, Angela Novelin; Sudana, I Putu; Negara, I Made Kusuma (Jurnal IPTA, 2023)
Komodo National Park. The purpose of this research is to find out the potential and packaging of marine tourism packages that have not been optimized in Komodo National Park.Data collection techniques in this study are observation, interviews, literature studies and documentation. The informant determination technique in this study is purposive sampling. The analysis technique used is qualitative descriptive. The results of this study show that in Komodo National Park there are fourteen potential Marine tourism. The marine tourism potential consists of Pink Beach, Siaba Besar, Kanawa Island, Batu Bolong, Kalong Island, Crystal Rock, Taka Makassar, The Cauldron, Manta Point, Kelor Island, Waecicu Beach, Pede Beach, Rangko Cave and Ujung Village. These potentials can be packaged into 3 tour packages, namely, Komodo Dive Tour with Full Day Tour activities, Labuan Bajo City Tour with Full Day Tour tourism activities and Komodo Oversea Tour with 3 day 2 tour activities Nights.